Pengaruh Harga, Kualitas Pelayanan Dan Kepuasan Konsumen Terhadap Loyalitas Pelanggan Hazel Salon Bridal Dan Spa - Wibowo, Debora Tata; Achmad, Nur (Pascasarjana STIE Amkop Makassar, 2025)
Finding out how big of an impact factors like pricing, service quality, and customer pleasure have on customer loyalty at Hazel Salon Bridal and SPA is the main goal of this research. To gather data, this research used a quantitative technique based on questionnaires. A total of 1,122 people who were at least fifteen years old, had been to the salon at least twice, and had used at least one service were included in the sample. Hypothesis testing is part of the analysis process which also includes multiple linear analysis, t and f tests, and determinant coefficient tests. This study found that: (1) The loyalty of Hazel Salon Bridal & SPA clients is greatly influenced by price. Customers tend to be more loyal if the price offered is reasonable and in accordance with the level of service; (2) With a p value of 0.001 and tcount of 3.824 > ttable 1.982, it is clear that high-quality service at Hazel Salon Bridal and SPA significantly affects client loyalty. Customer loyalty is directly proportional to service quality, which includes qualities such as friendliness, attention, and empathy; (3) With a significance value of 0.001 and tcount of 4.755 > ttable of 1.982, customer happiness has a significant effect on customer loyalty at Hazel Salon Bridal and SPA. This shows that customer loyalty is directly proportional to customer satisfaction; (4) The impact of price (X1), service quality (X2), and customer happiness on customer loyalty (Y) is greater than the Fcount value of 22.305, which is greater than the Ftable of 22.305. Therefore, the combined impact of the three independent factors on consumer loyalty is statistically significant. Keywords: Price; Service Quality; Customer Satisfaction; Customer Loyalty